High-quality draft genome sequence of Flavobacterium suncheonense GH29-5T (DSM 17707T) isolated from greenhouse soil in South Korea, and emended description of Flavobacterium suncheonense GH29-5T. Issue 1 (December 2016) - Tashkandy, Nisreen; Sabban, Sari; Fakieh, Mohammad; Meier-Kolthoff, Jan; Huang, Sixing; Tindall, Brian; Rohde, Manfred; Baeshen, Mohammed; Baeshen, Nabih; Lapidus, Alla; Copeland, Alex; Pillay, Manoj; et al.
Abstract Flavobacterium suncheonense is a member of the familyFlavobacteriaceae in the phylumBacteroidetes . Strain GH29-5T (DSM 17707T ) was isolated from greenhouse soil in Suncheon, South Korea.F. suncheonense GH29-5T is part of theG enomic E ncyclopedia of B acteria and A rchaea project. The 2, 880, 663 bp long draft genome consists of 54 scaffolds with 2739 protein-coding genes and 82 RNA genes. The genome of strain GH29-5T has 117 genes encoding peptidases but a small number of genes encoding carbohydrate active enzymes (51 CAZymes). Metallo and serine peptidases were found most frequently. Among CAZymes, eight glycoside hydrolase families, nine glycosyl transferase families, two carbohydrate binding module families and four carbohydrate esterase families were identified. Suprisingly, polysaccharides utilization loci (PULs) were not found in strain GH29-5T . Based on the coherent physiological and genomic characteristics we suggest thatF. suncheonense GH29-5T feeds rather on proteins than saccharides and lipids.